Rare Complication during Retinal Detachment Surgery: A Case Report - Iqra Mushtaq; Rutuja Patil; Nilesh Giri (Journal of Clinical and Diagnostic Research)
Retinal Detachment (RD) surgery, though routinely performed, carries the risk of rare but significant intraoperative complications that can affect surgical success. One such complication is subretinal air migration during fluid–air exchange, which can hinder retinal reattachment. We report a case of a 69-year-old man with progressive vision loss in the right eye over six months, diagnosed with Rhegmatogenous Retinal Detachment (RRD) involving a large horseshoe tear. The patient underwent Pars Plana Vitrectomy (PPV), during which the doctor peeled the membrane, used endolaser photocoagulation, performed a fluid–air exchange, and planned to use silicone oil as a tamponade. During the fluid–air exchange, an air bubble inadvertently entered the subretinal space and migrated to the posterior pole, where it was inaccessible for removal. This complication interfered with proper retinal reattachment and impacted the surgical outcome. The case highlights the need for surgical caution in managing large retinal tears and emphasises the importance of recognising and preventing subretinal air migration to optimise postoperative results in complex RD surgeries.